A guide to selecting high-performing antibodies for Serine/threonine-protein phosphatase 2A 56 kDa regulatory subunit delta isoform (PPP2R5D) for use in Western Blot, immunoprecipitation and immunofluorescence [version 2; peer review: 2 approved] - Carl Laflamme; Kathleen Southern; Riham Ayoubi; Maryam Fotouhi; Charles Alende (F1000Research)
Protein phosphatase 2A is a serine/threonine phosphatase with activity dependent on an associated regulatory subunit, serine/threonine-protein phosphatase 2A 56 kDa regulatory subunit delta (δ) isoform (PPP2R5D). PPP2R5D is the δ isoform in the B56 family of regulatory subunits. Abundantly expressed in the brain and involved in a broad range of cellular processes, PPP2R5D plays an essential role in modulating key neuronal pathways and signalling. Pathogenic mutations in the PPP2R5D gene are linked to clinical symptoms characterized by neurodevelopmental delay, intellectual disability, and autism spectrum disorders. The etiology of these genetic disorders remains unknown, which can partly be due to the lack of independently characterized antibodies. Here we have characterized six PPP2R5D commercial antibodies for Western Blot, immunoprecipitation, and immunofluorescence using a standardized experimental protocol based on comparing read-outs in knockout cell lines and isogenic parental controls. These studies are part of a larger, collaborative initiative seeking to address antibody reproducibility by characterizing commercially available antibodies for human proteins and publishing the results openly as a resource for the scientific community. While use of antibodies and protocols vary between laboratories, we encourage readers to use this report as a guide to select the most appropriate antibodies for their specific needs.